Serum gamma-glutamyltransferase and the burden of atherosclerosis in patients with acute coronary syndrome - Serkan Öztürk; Alim Erdem; Mehmet Fatih Özlü; Selim Ayhan; Kemalettin Erdem; Mehmet Özyaşar; Yusuf Aslantaş; Mehmet Yazıcı (KARE Publishing, 2013)
Objectives: It is well known that inflammation plays a key role in both initiation and propagation of acute coronary syndrome (ACS). White blood cell (WBC) and its subtypes are an indicator of inflammation in patients with ACS. We aimed to evaluate the WBC and its subtypes in patients aged <45 year with acute coronary syndromes. Study design: We retrospectively analyzed WBC and its subtypes (including neutrophil and lymphocyte) in 84 patients (<45 year) who were admitted to the emergency department for chest pain suggestive of ACS (44 unstable angina pectoris, 40 non-ST-segment elevation myocardial infarction [NSTEMI]), and 40 healthy controls. Results: Hypertension, diabetes mellitus, smoking, and family history were significantly higher in NSTE-ACS patients. Also, LDL levels was significantly higher and HDL levels was significantly lower in NSTE-ACS patients (p=0.041 and p=0.009). The difference in percent of lymphocytes between the groups was significant (p=0.048). N/L ratio was significantly different between all groups and between the NSTEMI and USAP (p<0.001 and p=0.041). Our results demonstrated that hypertension, percent of neutrophils, and N/L ratio was a significant independent predictor of NSTE-ACS (Beta=0.251, 95% CI=0.002-0.523, p=0.048; beta=0.561, 95% CI=0.008-0.137, p=0.028 and beta=0.260, 95% CI=0.042-0.438, p=0.018, respectively). Conclusion: N/L was found to be elevated in young patients with NSTE-ACS compared with control group. The inflammation assessed using WBC and its subtypes may be more important in young NSTE-ACS patients.